PROBLEMATIKA KEPEMIMPINAN DI LEMBAGA PENDIDIKAN ISLAM - Rifki Ahda Sumantri (Istitut Ilmu Al-Qur'an (IIQ) An-Nur Yogyakarta Komplek PP An Nur Ngrukem PO BOX 135 Bantul 55702 Yogyakarta Tlp/Fax (0274) 6469012. http://jurnalannur.ac.id/, 2013)
Problems of leadership in Islamic educational institutions have important aspects, able to understanding we needs to know: definitions of leadership, the natures and types of leadership, leadership styles, the main tasks of leadership, problems in Islamic educational institutions themselves, as well as leadership in Islamic educational institutions in the constellation national education policy. This problem will become a point of discussion here on the pillowcase. The problems of leadership in Islamic educational institutions, among others: autocratic style of leadership, poor delegation of authority from leader to subordinates, poor conflict of management, the lack of motivation and leader of the main tasks of a leader who was not realized.